ChemInform Abstract: Enantioselective [4 + 2]‐Annulation of Oxadienes and Allenones Catalyzed by an Amino Acid Derived Phosphine: Synthesis of Functionalized Dihydropyrans. Issue 37 (August 2016) - Ni, Huanzhen; Yao, Weijun; Waheed, Abdul; Ullah, Nisar; Lu, Yixin
Abstract: The optimized conditions including a L‐valine‐derived phosphine catalyst (PAM) allow the synthesis of a wide variety of dihydropyrans in high yields and excellent enantioselectivities.